(untitled) (Russian Medical and Social Journal, 2019)
Introduction. Modern technologies make it possible not only to plan reconstructive surgery virtually, but also to manufacture templates for resection and osteotomy, customized titanium plates based on the results of planning. Objective. To analyze the results of application of additive technologies for planning and performing reconstructive operations in the Maxillofacial Surgery and Stomatology Center at Burdenko Main Military Clinical Hospital Patients and Methods. 144 operations to eliminate different locations bone defects were performed in the Maxillofacial Surgery and Stomatology Center in 2007 - 2017. 136 patients (93%) had de-fects of the bones of the facial skeleton and the skull calvarium. In other cases, there were defects of the clavicle (2 patients), defects of the femur (2 patients), defects of the humerus (2 patients), a defect of the radius (1 patient), a defect of the navicular bone (1 patient). Results. Flaps were used to close the defects in 87% of cases (125 patients), and alloplastic implants were utilized in 13% of cases (19 patients). Additive technologies were used in 85% (n = 123) cases for planning the operation to eliminate defects, as well as for manufacturing surgical models and templates. Clinical cases are considered as examples of the use of the additive technologies for planning and performing reconstructive operations to close bone defects of different locations. The incidence of postoperative complications in the group of patients with facial skeleton and crani-al vault bones defects who underwent surgical interventions using templates was 26%, including minor complications - 17.5%, large - 8.5%. Among minor complications, hematomas (5%) and sup-puration (5%) of the recipient wound prevailed, less often similar complications were hematomas (4%) and suppuration (3%) of the donor wound. Large complications were represented by cases of complete (4%) or partial (5%) transplant necrosis. During surgical interventions without a template, it took significantly longer than the average time of grafting and graft formation (212 ± 18.7 min) than during operations with a template, including with a guide for drilling (136 ± 12.6 min, p